Barriers to participatory implementation of soil conservation projects: Perspectives and priorities. Issue 131 (May 2022) - Salehpour Jam, Amin; Tabatabaei, Mahmoud Reza; Mosaffaie, Jamal; Soltani, Mohammad Jafar; Shadmani, Alireza
Abstract: Awareness of People's Participation Barriers (PPBs) in the participatory implementation of Soil Conservation Projects (SCPs) is the prelude to promoting the levels of people's participation through relevant planning. This study aims to identify, classify, and prioritize barriers to people's participation in SCPs from the viewpoints of experts and the local community in the Vardij-Varish watershed, Iran. It also examines the agreement on the importance of PPBs in SCPs from the perspectives of both groups. In this study, 11 items were classified within the framework of demographic and planning components and related economic, social, executive, and educational-extension sub-components. PPBs were also prioritized based on Friedman's non-parametric test after confirming the validity and reliability of the questionnaire. Accordingly, ignoring people's income and centralization of decision-making power in the government organization were ranked as the most important PPBs in SCPs from the perspectives of 200 residents and 28 experts, respectively. Results indicate that the dominance of the top-down process and the lack of incentives and economic benefits are the most important PPBs. Based on the two-samples Kolmogorov-Smirnov test, the two groups had different perspectives on the importance of 64% of PPBs. In general, changing the approach from non-participatory watershed management to a participatory process and converging different perspectives through group decision-making are recommended to natural resource managers in the planning process to promote people's participation in SCPs. Graphical Abstract: ga1 Highlights: Barriers to participation were categorized into demographic and planning components. The planning component has the most PPBs in soil conservation projects. Experts and residents have different perspectives on the importance of 64% of PPBs. Experts consider the concentration of decision-making power as the most important PPB. Ignoring people's income is the most important PPB from the view of residents.